Gold Nanoclusters Exert Bactericidal Activity and Enhance Phagocytosis of Macrophage Mediated Killing of Fusobacterium nucleatum - Chen, Rixin; Qiao, Dan; Wang, Peng; Li, Lingjun; Zhang, Yangheng; Yan, Fuhua (Frontiers in Materials, 2021)
Fusobacterium nucleatum is a typical periodontal opportunistic pathogen that contributes to inflammatory diseases at oral or extra-oral sites. The emergence of antibiotics resistance calls for a substitute therapeutic strategy to control bacterial infections effectively. In addition, macrophage is an essential part of host defense against microorganism invasion in vivo. Herein, we synthesized gold nanoclusters (AuNCs) as potent antibacterial material to kill F. nucleatum through bactericidal behavior and pro-phagocytic activity. Firstly, we evaluated the bactericidal effect of AuNCs on F. nucleatum by the means of plate counting, growth curve measurement, bacterial viability analysis, and live/dead fluorescent imaging. Morphological changes and the intracellular reactive oxygen species levels of bacteria were further analyzed to explore the possible mechanisms. Additionally, the impact of AuNCs on the ability of macrophages to uptake bacteria under normal and inflammatory circumstance was also evaluated by fluorescent imaging. We found that AuNCs exhibited superior antibacterial performance on F. nucleatum in vitro by a combination of membrane disruption and oxidative stress. Furthermore, in the presence of AuNCs, macrophages displayed enhanced phagocytosis against F. nucleatum without inducing any significant cytotoxicity. Therefore, AuNCs are providing a new platform for the prevention and treatment of F. nucleatum-associated diseases.